2011
DOI: 10.1007/s00431-011-1563-x
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal agenesis: approach towards this severe diagnosis. Case report and review of the literature

Abstract: Tracheal agenesis (TA) is a severe congenital disorder with often an unexpected emergency presentation. There is complete or partial absence of the trachea below the larynx, with presence or absence of a tracheoesophageal fistula (TOF). A neonate with TA is described, and another 48 cases found in literature are reviewed. Due to absence of a TOF, five cases were diagnosed prenatally because of congenital high airway obstruction syndrome (CHAOS). When a TOF is present, polyhydramnion and several other congenita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
77
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(78 citation statements)
references
References 41 publications
(64 reference statements)
0
77
0
1
Order By: Relevance
“…Estimated incidence is 1 per 50 000 births, with a male-to-female ratio of 2:1 44 all of which were present in this case. Various factors, genetic and environmental, have been proposed, but no clear causation has been proven 4…”
Section: An and Stmentioning
confidence: 59%
See 1 more Smart Citation
“…Estimated incidence is 1 per 50 000 births, with a male-to-female ratio of 2:1 44 all of which were present in this case. Various factors, genetic and environmental, have been proposed, but no clear causation has been proven 4…”
Section: An and Stmentioning
confidence: 59%
“…Flody’s classification system is most commonly used and separates TA into three types4:Type 1: oesophagus connected to distal trachea via fistula (incidence 11%).Type 2: oesophagus connected to carina via fistula (incidence 61%).Type 3: two main bronchi arise from oesophagus (incidence 23%). …”
Section: An and Stmentioning
confidence: 99%
“…Less than 200 cases have been published [3]. During the first eight weeks of gestations, the tracheopulmonary complex develops from the respiratory diverticulum at the ventral aspect of the primitive foregut.…”
Section: Discussionmentioning
confidence: 99%
“…Its prevalence is less than 1:50,000 with a male to female ratio of 2:1 [2,3]. It was initially described in 1900 by Payne and only few cases were published worldwide [1].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent literature review, de Groot‐van der Mooren (2012) and colleagues reported that in 72% of cases, polyhydramnios was present in fetuses with tracheal atresia (TA) and a TOF, and in more than half of these cases there were no other mechanisms for polyhydramnios. They suggested that the diagnosis of TA should be considered when polyhydramnios develops, particularly in combination with associated anomalies 4 .…”
Section: Discussionmentioning
confidence: 99%